PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA PEGAWAI PADA DINAS KELAUTAN DAN PERIKANAN PROVINSI BENGKULU - Nyoman Jepri Arianto; Ida Anggraini; Nia Indriasari (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
The purpose of this research is to find out how the influence of rewards and sanctions on the performance of workers in the Department of Maritime Affairs and Fisheries of Bengkulu Province. Describe-and-calculate is the type used here. This data collection method uses observation techniques and questionnaires, with a sample of 90 respondents. The results of this study indicate multiple linear regression Y = 4.750 + 0.432 (X1) + 0.370 (X2) + 8.374. Where the coefficient is positive, meaning that there is a positive or unidirectional relationship between the variable Reward (X1) Punishment (X2) on employee performance at the Marine and Fisheries Service of Bengkulu Province. The results of the t test for the Reward variable (XI) show tcount 2.393 > ttable 1.660 and a significance of 0.019 <0.05, then the results of the hypothesis Ha are accepted and Ho are rejected, meaning Reward (XI) has a positive and significant effect on employee performance at the Provincial Maritime Affairs and Fisheries Service Bengkulu, while the results of the t test variable Punishment (X2) show tcount 4.476 > ttable 1.662 and significance 0.000 <0.05, then the results of the hypothesis Ha are accepted and Ho are rejected, meaning Punishment (X1) has a positive and significant effect on employee performance at the Maritime Service and Fisheries of Bengkulu Province. Then the results of the comparison of the Fcount value with Ftable, then the Fcount value is greater than the Ftable value, namely 14.830 > 2.71. This means that there is a simultaneous influence between Reward (XI) and Punishment (X2) on employee performance variables (Y) at the Maritime Affairs and Fisheries Service of Bengkulu Province.